Influence of magnetic field on electro-rheological Rayleigh-Taylor instability in composite couple-stress fluids and fluid saturated porous layer - Krishna B. Chavaraddi; Priya M. Gouder; Nagaraj N. Katagi; G.K. Ramesh (International Journal of Thermofluids)
The present study focuses on electro-rheological Rayleigh-Taylor instability (ERTI) at the interface between the thin fluid shell and a densely packed, weakly conducting, saturated porous layer subjected to electromagnetic acceleration. A dispersion relation is developed in order to do normal mode analysis. The findings demonstrate that the development rate of the unstable fluid is significantly delayed in the presence of electric and magnetic fields, as well as the influence of the couple-stress parameter. These are significant in many of the real-world scenarios explored in this study because they contribute to stabilize the interface.